An introduction to timber engineering - Andrews, H. J. (Monographs on furniture and timber ;, 1967)
Pergamon Series of Monographs on Furniture and Timber, Volume 10: An Introduction to Timber Engineering presents in readable form an understanding of timber engineering, which covers important aspects of the building industry particularly in the field of prefabrication. The chapters of this book present a good understanding of the many integrated divisions of the industry involved in timber engineering. The examples provided on design indicate the method of adapting normal structural analysis for use with timber and joint forms. Most of the information specified in this volume are British prac.